Targeted editing of rice genome for enhanced yield: Progress and prospects - Shobica Priya, Ramasamy; Raveendran , Muthurajan; Geetha , Seshadri; Manonmani, Swaminathan; Kalaimagal , Thiyagarajan; Deepa, Jaganathan; Balakrishnan , Natarajan; Gopalakrishnan, Chellappan; Sudha , Manickam; Sakthi Ambothi , Rathnasamy (Plant Science Today, 2025)
Rice is a staple food grain and its yield has undergone two major leaps, first during the 1960’s through improving the harvest index by introducing semi-dwarf trait and secondly through the introduction of hybrids during the 1980’s. However, yields have plateaued in the past decade, even as the growing population necessitates doubling rice production by 2050. Hence, genetic enhancement of yield potential in rice has become mandatory in rice-breeding programs, which can be achieved by mining novel yield genes from wild species, manipulating photosynthetic traits (e.g., C4 rice), or creating novel alleles through targeted mutagenesis. The available genome of the Nipponbare rice genome and the 3K Rice Genome Project have identified beneficial alleles and valuable accessions for breeding. Progress towards C4 rice highlights the need for photosynthetic trait manipulation to improve yields. However, the labor and time required stimulate breeders towards new technologies like genome editing. The CRISPR system offers a simpler, faster method to alter desired traits, with numerous candidate genes for grain yield. Rice, with its relatively small genome and strong synteny with other cereals, serves as an ideal model for the development of novel gene editing technologies. This review unveils an up-to-date investigation of rice genome editing for yield-related traits, with a focus on recent advancements, emerging trends and future directions to address the key challenges and opportunities in enhancing rice productivity. Future advancements in CRISPR-based multiplex editing, epigenome engineering and AI-driven predictive breeding will accelerate rice yield improvements, ensuring sustainable production to meet global food security demands by 2050.